Fetal thigh and upper-arm volumes by three-dimensional ultrasound to predict low postnatal body mass index. (30th July 2014) - Cavalcante, Rafael Oliveira; Caetano, Ana Carolina Rabachini; Nacaratto, Daniela Cristina; Helfer, Talita Micheletti; Martins, Wellington P.; Nardozza, Luciano Marcondes Machado; Moron, Antonio Fernandes; Araujo Júnior, Edward
Abstract: Objective : To assess the usefulness of estimating fetal upper arm and thigh volumes as predictors of low postnatal body mass index (BMI) using three-dimensional ultrasonography (3DUS) with extended imaging virtual organ computer-aided analysis (XI VOCAL). Methods : This prospective cross-sectional study analyzed 300 singleton pregnancies between 33 and 41 weeks of gestation. The Hadlock 4 formula was used to estimate fetal weight. The XI VOCAL 10 planes method was used to assess fetal upper arm and thigh volumes. After delivery, the newborns' BMI was evaluated and considered low (≤10th percentile) or normal (>10th percentile). We determined receiver operating characteristics (ROC) curves and respective areas under the curves for the percentiles of fetal weight and fetal thigh and upper arm volumes. Results : Of the 300 newborns, BMI was ≤10th percentile for 21 and >10th percentile for 279 newborns. The area under the ROC curve for fetal weight, obtained using the Hadlock formula, and fetal upper arm and thigh volumes, obtained by 3DUS, were 0.801, 0.930 and 0.924, respectively. We determined the sensitivity and specificity of the three parameters for predicting low postnatal BMI and found values of 85.70% and 65.60%, respectively, for fetal weight, 90.48% and 88.17%, respectively, for fetal thigh volume, and 76.19% and 92.47%, respectively, for fetal upper arm volume. Conclusion : Fetal upper arm and thigh volumes estimated using 3DUS with XI VOCAL were effective predictors of low postnatal BMI.